Aridity and cold temperatures drive divergent adjustments of European beech xylem anatomy, hydraulics and leaf physiological traits. (14th March 2022) - Vicente, Eduardo; Didion-Gency, Margaux; Morcillo, Luna; Morin, Xavier; Vilagrosa, Alberto; Grossiord, Charlotte
Abstract: Understanding plant trait coordination and variance across climatic gradients is critical for assessing forests' adaptive potential to climate change. We measured 11 hydraulic, anatomical and leaf-level physiological traits in European beech ( Fagus sylvatica L.) along a moisture and temperature gradient in the French Alps. We assessed how traits covaried, and how their population-level variances shifted along the gradient. The intrapopulation variances of vessel size and xylem-specific conductivity reduced in colder locations as narrow vessels were observed in response to low temperature. This decreased individual-level water transport capacity compared with the warmer and more xeric sites. Conversely, the maximum stomatal conductance and Huber value variances were constrained in the arid and warm locations, where trees showed restricted gas exchange and higher xylem-specific conductivity. The populations growing under drier and warmer conditions presented wide variance for the xylem anatomical and hydraulic traits. Our results suggest that short-term physiological acclimation to raising aridity and heat in southern beech populations may occur mainly at the leaf level. Furthermore, the wide variance of the xylem anatomical and hydraulic traits at these sites may be advantageous since more heterogeneous hydraulic conductivity could imply populations' greater tree–tree complementarity and resilience against climatic variability. Our study highlights that both intrapopulation trait variance and trait network analysis are key approaches for understanding species adaptation and the acclimation potential to a shifting environment.